The African National Congress and local democracy : the role of the ANC branch in Manzini- Mbombela. - Malabela, Musawenkosi Hemelton (My University, 2011)
The ANC constitution and some party legislative documents have noted the ANC branch as the basic unit of the organisation and that in all elective congresses, the branches make up 90 percent of all the delegates that participate in the election of the leaders of the party. The centrality of the branch in the organisation is marked by the fact that no member of the party can participate or hold any official position in the party without being a member of a branch. Dlamini (2010) offers a different view of the ANC branch when he speaks of the Polokwane Narrative and he argues that the ascendance of Jacob Zuma to the party’s throne as president of the party cannot be attributed to branches as many have claimed. Southall (2009) argues that the Zunami, which many have named the events leading up to the victory of Zuma in Polokwane, cannot solely be attributed to branches, but notes that the alliance partners- COSATU and SACP- played a role in the events leading to victory of the incumbent in Polokwane. Dlamini (2010) argues that branches are not as central as the ANC makes them out to be. The ANC notes that branches die between elections and elective congresses and are only revived at the dawn of these events. This study examines the ANC branch in order to understand what actually happens at an ANC branch and what are the challenges faced by the branch. This has been achieved through an investigation of one ANC branch- the Manzini branch which falls under the Mbombela Municipality and the Ehlandzeni Region of the ANC in rural Mpumalanga. This investigation was carried out through participant observation in branch ANC meetings, interviews with both branch leaders and ordinary members of the party and document analysis. The findings are those that attest to elite democracy theorists like Michels (1958) and the mobilisation and patronage functions of political parties discussed by Tordoff (1993). This research found that members of the ANC participate in branch activities, mostly mobilising for the party during election, because of the fact that their participation might be rewarded with a job in the municipality or government. I argue that these patronage networks that are forged through the branch explains why some members participate in branch activities even in between election and elective congresses, because their loyalty to the party might be rewarded. The strategic location of the branch in the midst of the people or communities I argue is one of the important factors that the ANC can explore to legitimise the party and for it to champion the needs of the people. This could only be achieved if the branch stops falling victim to manipulation by those individuals who have political ambitions who pump money into branches to influence election outcomes. This thesis also offers an understanding of the link between the ANC and ANC-led municipalities that the blurring of the party and the state is one that humps service delivery. As internal party squabbles are settled at the municipality, which affects the accountability of ANC councillors as they have to toe they party line or face being discipline which might end in a recall and loosing the perks that comes with the post of being a councillor. Thus accountability of councillors in communities is undermined by blurred line between the party and the state and this leads to lack of service delivery.